VULVODYNIA... The problem exists here! - Hameed, Nazli (Journal of Ayub Medical College Abbottabad, 2003)
A case of vulvodynia is being reported here. This is a frustrating disorder affecting young women. A 36 years old lady initially being treated non-specifically for vulval pain, dysparunia and vaginal discharge, for several months was investigated in the gynaecology unit of Combined Military Hospital, Rawalpindi. Examination was possible only under anaesthesia and biopsy report confirmed Erosive lichen Planus. After dermatological consultation she responded well to steroids. She was counselled about the risk of recurrence and small risk of malignancy Key words: Vulvodynia, Lichen planus